IO(X2Π)–Ar cluster: ab initio potential energy surface and dynamical computations. Issue 2 (13th December 2019) - Marzouk, S.; Ajili, Y.; Lique, F.; Ben El Hadj Rhouma, M.; Al Mogren, M. Mogren; Hochlaf, M.
Abstract : Spectroscopic and dynamical characterisation of IO–Ar cluster. Abstract : Iodine oxide (IO) is an important tropospheric molecule. In the present paper, we mapped the potential energy surfaces (PESs) of the doubly degenerate IO(X 2 Π)–Ar van der Waals system using single- and double-excitation coupled cluster approaches with non-iterative perturbation treatment of triple excitations [RCCSD(T)] extrapolated to the complete basis set (CBS) limit. In addition to bent local minima, we identified a linear Ar–IO complex as a global minimum. Afterwards, we performed scattering calculations on these PESs, considering the non-zero spin–orbit contribution and the Renner–Teller effect. The integral cross-sections exhibit an oscillatory structure vs. the final rotational state, as already observed for the NO(X 2 Π)–Ar system. Moreover, computations reveal that the Ar–IO complex is stable toward dissociation into IO and Ar. Therefore, it can be found in the atmosphere and participates in iodine compound physical chemical processes occurring there.